Makna Nilai-nilai Kultural Nahdlatul Ulama dalam Tinjauan Budaya Organisasi - Ihsani, A. Fikri Amiruddin; Febriyanti, Novi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2021)
This research discusses the meaning of the cultural values of Nahdlatul Ulama in the review of organizational culture. The purpose of this research is to describe, explain and find out the meaning of the cultural values of Nahdlatul Ulama in terms of organizational culture theory. This research uses qualitative research methods with a descriptive approach. The data collection techniques used were observation and documentation. The results of observations and documents that have been collected are then analyzed, compared and combined to form a systematic, coherent and complete study result. In this study, the results show that the meaning of the cultural values of Nahdlatul Ulama in the review of organizational culture is in accordance with the vision, mission and goals of the organization. The cultural values developed are known as al-Mabadi al-Khamsah which includes assidqu, al-amanah wal wafa'bil 'ahdi, al-'adalah, at-ta'awun and al-istiqamah. These cultural values are also manifested through traditions and amaliyah such as amar ma'ruf nahi munkar, aqiqah, diba'an, haul, istighosah, jam'iyahan, manakib, maulid Nabi, qunut, tahlil, tingkepan and grave pilgrimage. With the organizational culture and cultural values in it, it will be easier for an organization to achieve the vision, mission and goals aspired by its members, administrators and founders of the organization.